Malnutrition and experimental epilepsy - Gomes,Tâmara Kelly de Castro (2011)
INTRODUCTION: Disturbances in intrauterine environment can have harmful effects on the fetus and pathological consequences persisting throughout adolescence and adulthood. Protein restriction during the prenatal period has a significant impact on growth and development of the central nervous system. Food restriction increases the risk of neurological disorders such as epilepsy. OBJECTIVE: To relate the programming model by malnutrition and its implications in experimental epilepsy. Material and methods: There has been research papers published in the databases Medline, PubMed, CAPES journals, ScienceDirect and Scielo. The keywords selected for the study included epilepsy, Status Epilepticus, pilocarpine, malnutrition, programming. RESULTS AND DISCUSSION: Several studies in animal models or humans highlights the possible adverse effects of malnutrition at the onset of epileptic seizures. The vulnerability immunological, biochemical and electrolyte abnormalities and hypoglycemia may be the factors responsible for the intensification of the epileptogenic process in malnourished individuals. CONCLUSION: Malnutrition negatively changes the epileptogenic circuitry.